Iraq's Position on the Establishment of the Palestine Liberation Organization Army - JASIM, MUATH HILAL; ABBED ALESAWY, ALA ALDEEN ABBAS (Journal of Tikrit University for Humanities, 2023)
The study includes important subjects, the most important of which is Iraq’s position on the establishment of the PLO army in international forums, as Iraq participated in all Arab international conferences that led to the establishment of the PLO army, especially the Alexandria Conference. A number of members of the organization’s army in the Iraqi camps and were trained according to the contexts recognized in the Iraqi army, as well as a number of the organization’s army were accepted in the Military College and the Air Force College, in addition to that, Iraq provided financial and moral assistance to the organization’s army, and Iraq gave complete freedom to the organization’s army. In the field of travel and residence, Iraq granting them passports, the Iraqi government also issued the military service law, which stipulates that the organization’s army is treated as the Iraqi soldier and includes the reward for ending military service and vacations. The Iraqi government also granted Iraqi citizenship to members of the organization’s army who are married to Iraqi women, so we find that Iraq did not skimp on The Palestine Liberation Organization in terms of equipment and numbers to establish the PLO army.